Zdravotně technické a plynovodní instalace v ubytovacím zařízení - Kolář, Daniel (Vysoké učení technické v Brně. Fakulta stavební, 2025)
Diplomová práce se zabývá problematikou zdravotně technických instalací a plynovodu včetně návrhu přípojek vodovodu, kanalizace a plynovodu pro ubytovací zařízení. Součástí práce je koncepční řešení různých typů ohřevu teplé vody, které zohledňuje technické, ekonomické a environmentální aspekty.

The thesis addresses the issue of sanitary technical installations and gas pipelines, including the design of water supply, sewage, and gas pipeline connections for an accommodation facility. The thesis includes a conceptual solution for various types of hot water heating systems, taking into account technical, economic, and environmental aspects.
The Sanitary Installation and gas pipeline installation of the Hotel
Keywords: zdravotně technické instalace; plynovod; vodovod; kanalizace; ohřev teplé vody; ubytovací zařízení; technické řešení; projektová dokumentace; energetická účinnost; provozní náklady; distribuce vody; odpadní vody.; sanitary technical installations; gas pipeline; water supply; sewage; hot water heating; accommodation facility; technical solution; project documentation; energy efficiency; operational costs; water distribution; wastewater.